Compensating for age limits through emotional crossmodal integration - Chaby, Laurence; Boullay, Viviane Luherne-du; Chetouani, Mohamed; Plaza, Monique (Frontiers in Psychology, 2015)
Social interactions in daily life necessitate the integration of social signals from different sensory modalities. In the aging literature, it is well established that the recognition of emotion in facial expressions declines with advancing age, and this also occurs with vocal expressions. By contrast, crossmodal integration processing in healthy aging individuals is less documented. Here, we investigated the age-related effects on emotion recognition when faces and voices were presented alone or simultaneously, allowing for crossmodal integration. In this study, 31 young adults (M = 25.8 years) and 31 older adults (M = 67.2 years) were instructed to identify several basic emotions (happiness, sadness, anger, fear, disgust) and a neutral expression, which were displayed as visual (facial expressions), auditory (nonverbal affective vocalizations) or crossmodal (simultaneous, congruent facial and vocal affective expressions) stimuli. The results showed that older adults performed slower and worse than younger adults at recognizing negative emotions from isolated faces and voices. In the crossmodal condition, although slower, older adults were as accurate as younger except for anger. Importantly, additional analyses using the ‘race model’ demonstrate that older adults benefited to the same extent as younger adults from the combination of facial and vocal emotional stimuli. These results help explain some conflicting results in the literature and may clarify emotional abilities related to daily life that are partially spared among older adults.